Penggunaan Limbah Baglog Tiram dan Jenis Nutrisi Terhadap Pakcoy Pada Hidroponik Substrat - Retno Bandriyati Arni Putri; Trijono Djoko Sulistyo; Chairul Anwar (Agrosains : Jurnal Penelitian Agronomi, 2017)
The increase of oyster mushroom farmers in wonogiri will be impact immediately on increasing waste baglog. One of the utilization is to be medium on hydroponic substrate for growing mustard greens and it will combined with charcoal and various types of nutrients. The research was conducted from October to December 2015 at the Greenhouse C and Laboratory EMPT UNS.the research employed completely random design (CRD) with two factor that is ratio of medium and various types of nutrients. The result of research showed that interaction between ratio of medium and various types affected significantly  the parameters of leaf area, leaf fresh weight and leaf biomass. Root fresh weight, root volume, root length and root biomass is only influenced by the type of nutrition with the ab mix is the most good in improving and supplying nutrients